Prevalence of Overweight and Obesity Among Medical Students at the University of Mosul - Zaid Muayad Yassen; Anmar B. Al-Dewachi (Medical Journal of Babylon)
Background: Overweight and obesity are important reasons for mortality worldwide, Medical students are further susceptible to obesity due to their daily life with fewer hours of physical activity and disorderly food consumption habits. Objectives: The aim of this study was to evaluate the prevalence of overweight and obesity among medical students at the University of Mosul and to describe related dietary habits and physical activities. Materials and Methods: This study was conducted in the College of Medicine University of Mosul. A cross-sectional study design was selected. Messages were sent to 2179 students, and 1520 students agreed to participate with a response rate of 69.76%. A specially designed questionnaire form was filled out by each participant after a brief explanation of the study objectives. Anthropometric were measured including body weight and height. Body mass index was calculated as an indicator of overweight and obesity. Results: This study showed that more than three-quarters of the study population (79.54%) were between 18 and 24 years of age. Overweight and grade I obesity was observed among 21.05% and 4.48% of medical students, respectively. The study showed that overweight and grade I obesity were more prevalent in males than in females (27.66% and 7.09% in males compared to 17.15% and 2.93% in females, respectively) and this difference was found to be statistically highly significant. This study showed that approximately 78% of medical students stated that they practice exercise regularly. Conclusion: Obesity and overweight are more prevalent among male medical students than females.